“Always the same stairs, always the same room”: the uncanny architecture of Jean Rhys's Good morning, midnight - Zimmerman, Emma (Indiana University Press, 2015)
Jean Rhys’s Good Morning, Midnight (1939) is a novel that returns obsessively to the uncanny architecture of the Parisian hotel, through providing insight into the deracinated experiences of protagonist Sasha Jansen, a woman existing at the peripheries of the interwar city. Strikingly, this uncanny architecture structures the narrative itself, in the form of frequent disruptions in temporality, stylistic negotiations of memory, and distinct fragmented typography. An architectural interpretation of Sigmund Freud’s “The Uncanny” (1919) provides a useful interpretive lens for the novel, which helps to draw out how the uncanny functions — both thematically and formally — as a spatial and psychological symptom of the deracinated modern urban condition. Working in conjunction with Rhys’s representation of memory, the uncanny architecture of Good Morning, Midnight challenges contemporary spatial theorists who posit the hotel as a key site for the liberating eradication of history, whilst also evidencing Rhys’s literary innovations in the interwar period.